Cleaner production of thermal insulation boards utilizing buffing dust waste. (1st November 2019) - Hittini, Waseem; Mourad, Abdel-Hamid I.; Abu-Jdayil, Basim
Abstract: Buffing dust waste/polystyrene bundling insulating composite is developed. Different proportions of buffing dust (from 5 wt% up to 25 wt %.) were used. The blends were mixed using co-twine extruder prior exposing it to heat and pressure using hot press machine. The thermal, physical and mechanical properties of the composites were investigated. The prepared insulation composites display a better thermal performance than pure polystyrene insulation boards. This study shows that, adding of 10 wt % buffing dust to polystyrene composites reduces the thermal conductivity of the insulation board by 13%. All prepared composites have superior thermal conductivity (0.044–0.056 W/m-K), compression strength (11.55–8.23 MPa) and flexural strength (29.51–10.53 MPa) compared to conventional bundling thermal insulation materials without degrading the mechanical properties. Chemical treatment was applied to the buffing dust filler to improve the composite integrity. Thermogravimetric and FTIR analyses were used to study the effect of the chemical treatment of the fillers. The findings of this work prove that the developed composite can be used as an alternative insulating material in building sector. In addition, it reduces the environmental impact of both buffing hazardous waste and polystyrene and the used recycling solution contributes to the fulfilment of united nation sustainable development goals and cleaner production building insulation boards. Graphical abstract: Image 1 Highlights: Development of buffing dust-polystyrene composites as a new alternative thermal insulator. Buffing dust-polystyrene composites can be manufactured using extrusion and hot press technique. Buffing dust-polystyrene composites display better thermal performance than the pure polystyrene insulating material. Buffing dust-polystyrene composites have superior thermal conductivity (0.044–0.056 W/m-K) at room temperature. Chemical treatment of the buffing dust filler improves the composites flexure strengths.